PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VA SDN 110 PEKANBARU - Afdoli Putra; Lazim N Lazim N; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research supported by the low study results students, It can be seen from 42 students, only 11 students who been solved of average 65,86 while kkm set school is 76. The IPS study results students because a teacher often uses communication one direction and only focused teachers as information center that only transfers of course to students , so students passive and less enthusiastic in learning resulting in learning outcomes students in particular in learning IPS. As for the purpose of this research is to improve learning outcomes is social class a student of class VA SDN 110 Pekanbaru by applying role playing kind of classroom. This research is research class action, consisting of two cycle.Every cycle consisting of two meetings and once daily test at each end cycle. The subject of study this is a student of class VA SDN 110 Pekanbaru which consisted of 42 students , consisting of 23 as a boy and a girl that is in their 19. The research was conducted in the first half of the even in 2016 / 2017. Following the completion of the process of refinement kind of classroom learning by using role playing the activity of teacher at cycle I increased from 58,33 % with two categories of less , be 69,44 % with two categories of enough. Then in the cycle II rose again from 77,77 % with good category , be 91,66 % with two categories of very good .While the activity of the successful students at cycle i increased from 55,55 % with two categories of enough , be 66,66 % with two categories of enough. Then rose again in the cycle II of 77,77 % with good category , be 91,66 % with two categories of very good. Study results students increased from 65,86 be 75,96 in remedial daily I with the percentage increase 15,33 % and in remedial daily II become inflated again 83,21 with the increased 26,34 %Keywords: Role Playing Learning Model, Learning Result, Social Studies